Implementation Of Information Management System In Supporting Administrative Services At The Population And Civil Registration Services (DUKCAPIL) Gunungsitoli City - Delmanius Zebua; Fatolosa Hulu (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study discussed how the implementation of Information Management Systems in support of administrative services at the Department of Population and Civil Registration (Dukcapil) Gunungsitoli. Implementation of the Information Management System in support of administrative services at the Department of Population and Civil Registration (Dukcapil) Gunungsitoli. As well as having uses from various parties, both from the research site and from the author himself. Basically, this study uses descriptive qualitative research methods, using observation guidance instruments, interviews and documentation in data collection. Data analysed using methods of data collection, data reduction, data presentation, and conclusion. This study determines the subject and object of research with reference to the interview guidelines for conducting interviews, observations and and questionnaires as a complement. The results of this study indicate that the implementation of Management Information Systems in support of administrative services at the Department of Population and Civil Registration (Dukcapil) Gunungsitoli has been well implemented by using all facilities/ facilities and infrastructure as well as the application of SIAK as a stepping stone in optimizing the application of Management Information Systems. Efforts to improve the quality of service to the community are increasing because it is supported by a variety of administrative services more quickly and effectively